Co3O4/TiO2 catalysts studied in situ during the preferential oxidation of carbon monoxide: the effect of different TiO2 polymorphs. Issue 7 (2nd March 2023) - Nyathi, Thulani M.; Fadlalla, Mohamed I.; Fischer, Nico; York, Andrew P. E.; Olivier, Ezra J.; Gibson, Emma K.; Wells, Peter P.; Claeys, Michael
Abstract : This study reveals the influence of different TiO2 supports on the catalytic performance and phase transformations of Co3 O4 during CO-PrOx. Abstract : Co3 O4 nanoparticles were supported on different TiO2 polymorphs, namely, rutile, anatase, and a 15 : 85 mixture of rutile and anatase (also known as P25), via incipient wetness impregnation. The Co3 O4 /TiO2 catalysts were evaluated in the preferential oxidation of CO (CO-PrOx) in a H2 -rich gas environment and characterised in situ using PXRD and magnetometry. Our results show that supporting Co3 O4 on P25 resulted in better catalytic performance, that is, a higher maximum CO conversion to CO2 of 72.7% at 200 °C was achieved than on rutile (60.7%) and anatase (51.5%). However, the degree of reduction (DoR) of Co3 O4 to Co 0 was highest on P25 (91.9% at 450 °C), with no CoTiO3 detected in the spent catalyst. The DoR of Co3 O4 was lowest on anatase (76.4%), with the presence of Ti x O y -encapsulated CoO x nanoparticles and bulk CoTiO3 (13.8%) also confirmed in the spent catalyst. Relatively low amounts of CoTiO3 (8.9%) were detected in the spent rutile-supported catalyst, while a higher DoR (85.9%) was reached under reaction conditions. The Co 0 nanoparticles formed on P25 and rutile existed in the fcc and hcp crystal phases, while only fcc Co 0 was detected on anatase. Furthermore, undesired CH4 formation took place over the Co 0 present in the P25- and rutile-supported catalysts, while CH4 was not formed over the Co 0 on anatase possibly due to encapsulation by Ti x O y species. For the first time, this study revealed the influence of different TiO2 polymorphs (used as catalyst supports) on the chemical and crystal phase transformations of Co3 O4, which in turn affect its activity and selectivity during CO-PrOx.